Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4014/jmb.1711.11017
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Broad-host-range Bacteriophage Infecting Salmonella enterica subsp. enterica for Biocontrol and Rapid Detection

Abstract: Bacteriophages have gained substantial attention as biocontrol and biorecognition agents, substituting antibodies. In this study, a Enteritidis-specific bacteriophage, KFS-SE1, was isolated, identified, and characterized. This phage infects S. Enteritidis with high specificity. This phage is highly stable under various pH (5-11), temperature (4-60°C), and organic solvent conditions. The KFS-SE1 genome consisted of 59,715 bp with 73 predicted open reading frames and 57.14% GC content; it had a complete set of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, antibiotic treatment may no longer be the most effective method for the control of E. coli O157:H7 due to the sharp increase in antibioticresistant infections and strains as a result of the acquisition of genetic capacity [8] and alteration of the microbiome composition of host by antibiotic exposure [9]. Recently, bacteriophage (phage) treatment has emerged as a promising alternative to antibiotics [10,11]. Phages are viruses that have the ability to infect and kill target bacteria [12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, antibiotic treatment may no longer be the most effective method for the control of E. coli O157:H7 due to the sharp increase in antibioticresistant infections and strains as a result of the acquisition of genetic capacity [8] and alteration of the microbiome composition of host by antibiotic exposure [9]. Recently, bacteriophage (phage) treatment has emerged as a promising alternative to antibiotics [10,11]. Phages are viruses that have the ability to infect and kill target bacteria [12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…By contrast, the previously characterized C. rodentium phage phiCR1, which targets lipopolysaccharide (LPS) as a receptor, was shown to be highly species-specific infecting only C. rodentium and not closely related Enterobacteriaceae, including C. freundii and E. coli (30). Although, phiCR1 host range supports the general notion that phages are largely species-specific (38,39), several other phages infecting various Enterobacteriaceae (38,40,41) and staphylococci (42) have also been demonstrated to be polyvalent. Polyvalent phages infecting strains across genera raise a question as to their so called "optimal" host and whether a phage's host should be inferred by genomic relationships rather than bacterial strain plaquing in vitro (43).…”
Section: Discussionmentioning
confidence: 86%
“…Gencay et al (2019) determined that the combination of phage type and receptor is the main determinant of host spacing in their study of the characterization of Salmonella phages isolated from various sources [27]. Choi et al (2017) reported that two Salmonella phages isolated in their study degraded five Salmonella serotypes [28]. A total of 58 Salmonella phages were isolated from wastewater treatment plants, riverside wastewater, lakeside farm waste, and poultry in the Huang et al ( 2018) study [29].…”
Section: Discussionmentioning
confidence: 99%